2022
DOI: 10.3389/fpubh.2022.1008521
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pfizer/BioNTech and Sinopharm COVID-19 vaccines in reducing hospital admissions in prince Hamza hospital, Jordan

Abstract: BackgroundThere is a need to establish the effectiveness of the coronavirus disease 2019 (COVID-19) vaccines in reducing COVID-19-related hopitalization of patients in Jordan. As the vaccination program accelerates, it is important to determine whether the vaccines' effectiveness (VE) has successfully reduced the number of acute cases admitted to hospital.MethodsTo determine the efficacy of Pfizer-BioNTech and Sinopharm COVID-19 vaccines among Jordanian patients admitted to Prince Hamza hospital, a single cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…The participants here predominantly received the Pfizer and Moderna vaccines, which may be particularly efficient at evoking a durable anti-RBD response. Similar observations were made by several studies, that participants who received the Sinopharm vaccine (whole virus) had lower antibody levels compared with Pfizer/Moderna vaccine (spike protein) 53 54. mRNA vaccine candidate also induces higher cellular immune responses than the recombinant protein vaccine.…”
Section: Discussionsupporting
confidence: 84%
“…The participants here predominantly received the Pfizer and Moderna vaccines, which may be particularly efficient at evoking a durable anti-RBD response. Similar observations were made by several studies, that participants who received the Sinopharm vaccine (whole virus) had lower antibody levels compared with Pfizer/Moderna vaccine (spike protein) 53 54. mRNA vaccine candidate also induces higher cellular immune responses than the recombinant protein vaccine.…”
Section: Discussionsupporting
confidence: 84%
“…Figure 2. Distribution of studies selected for the efficacy of the Sinopharm, CoronaVac, and Covaxin vaccines for the prevention of COVID-19[10,11,14,15,[29][30][31][32][34][35][36][37][40][41][42][43][44][47][48][49].…”
mentioning
confidence: 99%
“…Understanding vaccine effectiveness by vaccine suppliers can guide individual choices and policy recommendations regarding the continued administration of coronavirus vaccines and subsequent boosters to provide substantial and significant protection against COVID-19 hospitalization. [14] In the present study, the participants were between 31 and 60 years of age, and 11% were older than 50 years. In line with the data from this study, another study reported that administering a booster dose of Pfizer BioNTech to adults who received a primary course of the same vaccine is associated with a major reduction in the risk of confirmed and severe disease due to COVID-19.…”
Section: Discussionmentioning
confidence: 67%
“…Understanding vaccine effectiveness by vaccine suppliers can guide individual choices and policy recommendations regarding the continued administration of coronavirus vaccines and subsequent boosters to provide substantial and significant protection against COVID-19 hospitalization. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%